2022
DOI: 10.3390/buildings12091344
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Acoustic Correction of a Multipurpose Performance Hall: The Italian Theatre “Cavallino Bianco”

Abstract: This study presents the retrofit acoustic design of the Italian theatre “Cavallino Bianco”. In its historical configuration, the hall had a curved roof with a pressed-plant fiber ceiling, which was demolished and replaced with a wooden roof without a false ceiling, leading to an increase in volume and worsening of the reverberation time. This study proposes the realization of a wave ceiling and the application of sound-absorbing and reflecting panels on the walls, which have already been implemented. These mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the studies by Gino Iannace [25] and Maria Grazia De Giorgi et al [26], natural fibers with good sound absorption coefficients were reported that were similar to synthetic porous materials, and upon increasing the sample thickness, the highest values of the sound absorption coefficient moved towards the lowest frequencies with diverse applications, including building restorations for sound isolation.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies by Gino Iannace [25] and Maria Grazia De Giorgi et al [26], natural fibers with good sound absorption coefficients were reported that were similar to synthetic porous materials, and upon increasing the sample thickness, the highest values of the sound absorption coefficient moved towards the lowest frequencies with diverse applications, including building restorations for sound isolation.…”
Section: Introductionmentioning
confidence: 99%